The Effectiveness of Teaching Kids Athletics Program for Young Children in the Content of Physical Education Curricula in Sultanate of Oman from the point of view of Physical Education Teachers - Majid AL Busafi; Samir bin Issa bin Muhammad Al-Sulaimi (College of Physical Education and Sport Sciences, 2021)
This study aimed to identify the effectiveness of teaching the athletics program for young children (Kids Athletics) in the content of school PE curricula for grades (1-4) in the Sultanate of Oman from the point of view of PE teachers. To achieve the objectives of the study, the researchers used the descriptive approach by applying a questionnaire to measure the effectiveness of teaching the athletics program for young children on a sample of (378) male and female teachers for grades (1-4) in different educational governorates. The study found that the degree of effectiveness of teaching the athletics program for young children (Kids Athletics) from the teachers' point of view is very large, reaching (4.30) and that the degree of teachers' awareness of the program is very large, reaching (4.20), and the responses of the sample members about the availability of program implementation requirements reached (3.81), and there were no statistical differences at the level of significance (α = 0.05) between the arithmetic averages of teachers' responses to the effectiveness of teaching the program and teachers' awareness about the program according to academic qualifications and years of experience for teachers due to the variables of academic qualifications and years of experience for teachers. In light of the results of the study, the researchers recommend the importance of including the athletics program for youngsters (Kids Athletics)  in the curricula of the fifth and sixth grades of the school PE subject due to its importance and contribution to achieving the objectives of the subject and developing motor abilities, and the need to continue in the qualifying and training programs to develop the capabilities of PE teachers in teaching the program and to ensure that schools are equipped with the necessary equipment to teach the suggested program, and provide the requirements for its implementation within the academic units of the curriculum.